PERLINDUNGAN HUKUM BAGI PEMBERI FIDUSIA TERKAIT PENCANTUMAN KLAUSUL YANG BERPOTENSI MERUGIKAN PEMBERI FIDUSIA DALAM PERJANJIAN JAMINAN FIDUSIA. (STUDI PADA PT. CAPELLA MULTIDANA CABANG MEDAN) - Situmorang, Reward; Purba, Hasim; Harianto, Dedi; Devi, Keizerina (BULETIN KONSTITUSI, 2022)
The Clauses specified in the Fiduciary Collateral Contract potentially harm the fiduciary givers and are contrary to the prevailing legal provisions such as the clause which states that debt collectors can come into the places where the collateral is kept any time, the clause which gives the authority to do anything, the clause which gives absolute power of attorney, the clause about the seizing of fiduciary collateral, and the clause about the cost of making notarial deeds and fiduciary registration. It is also found that there is legal protection for fiduciary givers such as prohibition to make clauses as specified in Article 18 of Law on Consumer Protection, Article 33 of Law on Fiduciary Collateral, the Supreme Courts Ruling No. 18/2019 and prohibition of business people on the Transfer of Liability (Regulation of OJK No I/POJK.07/2013 on Consumer Protection in Financial Service Sector. Beside that, the Fiduciary givers can report and file a complaint to BPSK, OJK, and the Court. Finally, it is found that the liability of a Notary as the public official who makes the contract which potentially harm the Fiduciary givers. His liability is in the civil law (specified in Article 84 and Article 65 of Law No. 2/2014) and in the administrative law ( specified in Article 65 A of Law No. 2/2014).